A concept of dual-responsive prodrugs based on oligomerization-controlled reactivity of ester groups: an improvement of cancer cells versus neutrophils selectivity of camptothecin - Klemt, Insa; Reshetnikov, Viktor; Dutta, Subrata; Bila, Galyna; Bilyy, Rostyslav; Cuartero, Itziar Cossío; Hidalgo, Andrés; Wünsche, Adrian; Böhm, Maximilian; Wondrak, Marit; Kunz-Schughart, Leoni A.; Tietze, Rainer; et al. (RSC Medicinal Chemistry, 2024)
Many known chemotherapeutic anticancer agents exhibit neutropenia as a dose-limiting side effect. In this paper we suggest a prodrug concept solving this problem for camptothecin (HO-cpt). The prodrug is programmed according to Boolean “AND” logic. In the absence of H2O2 (trigger T1), e.g. in the majority of normal cells, it exists as an inactive oligomer. In cancer cells and in primed neutrophils (high H2O2), the oligomer is disrupted forming intermediate (inactive) lipophilic cationic species. These are accumulated in mitochondria (Mit) of cancer cells, where they are activated by hydrolysis at mitochondrial pH 8 (trigger T2) with formation of camptothecin. In contrast, the intermediates remain stable in neutrophils lacking Mit and therefore a source of T2. In this paper we demonstrated a proof-of-concept. Our prodrug exhibits antitumor activity both in vitro and in vivo, but is not toxic to normal cell and neutrophils in contrast to known single trigger prodrugs and the parent drug HO-cpt.
CRIS-Team Scopus Importer:2024-04-19

Mitochondria-Catalyzed Activation of Anticancer Prodrugs - Raucheisen, Michael; Attia, Dina; Körber, Marlies; Crevillén, Alejandra Aroca; Hidalgo, Andrés; Beierlein, Frank; Imhof, Petra; Mokhir, Andriy (ChemCatChem, 2025)
Mitochondria mediate electron transport chain (ETC) to power ATP synthase. In cancer cells, the ETC is disturbed leading to leakage of electrons that ultimately results in generation of H2O2. This difference between cancer and healthy cells can be used for the design of cancer-specific prodrugs as confirmed in several proof-of-concept studies. Unfortunately, the known prodrugs are either insufficiently cancer cell specific or their activation efficacy is low. In this work, we solved this problem by optimizing the conjugate of a drug camptothecin and a H2O2-responsive aminoferrocene to obtain the prodrug C. The multistep reaction of the prodrug C with H2O2 is >20-fold more efficient than that of the parent system. The prodrug is accumulated and activated in mitochondria of cancer cells in a H2O2-dependent fashion. The anticancer efficacy towards human ovarian cancer A2780 and monocytic leukemia THP1 cells is improved from 573 and >3000 nM (for prodrug B) to 142 and 479 nM (for prodrug C) correspondingly. Additionally to the excellent activity, the new prodrug is not toxic in vivo to a range of blood (red and white blood cells, neutrophils, monocytes, platelets) and bone marrow cells (monocytes, B and T cells and others) in contrast to camptothecin.
CRIS-Team Scopus Importer:2025-05-16
Keywords: Aminoferrocene; Anticancer; Catalysis; Mitochondria; Reactive oxygen species

Red Fluorescent Aminoferrocene (Pro)Drugs for in Cellulo and in Vivo Imaging - Chernii, Svitlana; Selin, Roman; Bila, Galyna; Bilyy, Rostyslav; Körber, Marlies; Mokhir, Andriy (Chemistry - A European Journal, 2024)
Red fluorescent dyes are usually charged, lipophilic molecules with relatively high molecular weight, which tend to localize in specific intracellular locations, e. g., a cyanine dye Cy5 is biased towards mitochondria. They are often used as markers of biomolecules including nucleic acids and proteins. Since the molecular weight of the dyes is much smaller than that of the biomolecules, the labelling has a negligible effect on the properties of the biomolecules. In contrast, conjugation of the dyes to low molecular weight (pro)drugs can dramatically alter their properties. For example, conjugates of Cy5 with lysosome-targeting aminoferrocenes accumulate in mitochondria and exhibit no intracellular effects characteristic for the parent (pro)drugs. Herein we tested several neutral and negatively charged dyes for labelling lysosome-targeting aminoferrocenes 7 and 8 as well as a non-targeted control 3. We found that a BODIPY derivative BDP-TR exhibits the desired unbiased properties: the conjugation does not disturb the intracellular localization of the (pro)drugs, their mode of action, and cancer cell specificity. We used the conjugates to clarify the mechanism of action of the aminoferrocenes. In particular, we identified new intermediates, explained why lysosome-targeting aminoferrocenes are more potent than their non-targeted counterparts, and evaluated their distribution in vivo.
CRIS-Team Scopus Importer:2024-08-16
Keywords: Cancer; Drug; Imaging; Prodrug; Red fluorescent dye